On robust strong‐non‐interferent low‐latency multiplications - Maria Chiara Molteni; Jürgen Pulkus; Vittorio Zaccaria (IET Information Security)
Abstract The overarching goal of this work is to present new theoretical and practical tools to implement robust−t−probing security. In this work, a low‐latency multiplication gadget that is secure against probing attacks that exploit logic glitches in the circuit is presented. The gadget is the first of its kind to present a 1‐cycle input‐to‐output latency while belonging to the class of probing security by optimized composition gadgets [6]. In particular, the authors show that it is possible to construct robust‐t‐strong‐non‐interferent gadgets without compromising on latency with a moderate increase in area. The authors provide a theoretical proof for the robustness of the gadget and show that, for t≤4, the amount of randomness required can even be reduced without compromising on robustness.